2002
DOI: 10.1242/dev.129.9.2181
|View full text |Cite
|
Sign up to set email alerts
|

Cdx1andCdx2have overlapping functions in anteroposterior patterning and posterior axis elongation

Abstract: Mouse Cdx and Hox genes presumably evolved from genes on a common ancestor cluster involved in anteroposterior patterning. Drosophila caudal (cad) is involved in specifying the posterior end of the early embryo, and is essential for patterning tissues derived from the most caudal segment, the analia. Two of the three mouse Cdx paralogues, Cdx 1 and Cdx2, are expressed early in a Hox-like manner in the three germ layers. In the nascent paraxial mesoderm, both genes are expressed in cells contributing first to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(24 citation statements)
references
References 64 publications
(20 reference statements)
3
21
0
Order By: Relevance
“…Although our elongating system recapitulates some of this pattern and initiates expression of relatively posterior HOX profiles, we did observe day-to-day fluctuations in HOX gene expression via bulk sequencing. Wnt and FGF signaling have been shown to specify brachial and thoracic HOX identity by upregulating expression of the transcription factor CDX2, which allows for HOX1-HOX9 expression, forming a posterior axial identity (Mazzoni et al, 2013;Metzis et al, 2018;van den Akker et al, 2002) In our system, high expression of FGF17, WNT5B and CDX2 were observed starting at day 1 through day 3 in the 4uM CHIR treated organoids, consistent with early expression of HOX genes (Fig. 6).…”
Section: Discussionsupporting
confidence: 77%
“…Although our elongating system recapitulates some of this pattern and initiates expression of relatively posterior HOX profiles, we did observe day-to-day fluctuations in HOX gene expression via bulk sequencing. Wnt and FGF signaling have been shown to specify brachial and thoracic HOX identity by upregulating expression of the transcription factor CDX2, which allows for HOX1-HOX9 expression, forming a posterior axial identity (Mazzoni et al, 2013;Metzis et al, 2018;van den Akker et al, 2002) In our system, high expression of FGF17, WNT5B and CDX2 were observed starting at day 1 through day 3 in the 4uM CHIR treated organoids, consistent with early expression of HOX genes (Fig. 6).…”
Section: Discussionsupporting
confidence: 77%
“… 23 In the mouse cdx2 is essential for anteroposterior patterning of embryonal axis and morphogenesis of cloacal structures. 24 27 Strikingly, Cdx2 heterozygous conditional mutant mice show a variable phenotype that can include an imperforate anus, sirenomelia, posterior vertebral truncations, and bladder anomalies, 25 , 26 , 28 which is similar to the human clinical phenotype ( Table 1 ).…”
Section: Discussionmentioning
confidence: 94%
“…Variants in the HOXL gene CDX1 are associated with anorectal malformations. 33 CDX1 and CDX2 have overlapping functions in posterior axis elongation in mice 27 and have strong co-expression during anorectal morphogenesis in human embryos. 34 A mutation in the HOXL gene HOXD13 has been linked to VACTERL.…”
Section: Discussionmentioning
confidence: 99%
“…1C). After four days of differentiation, we stained the differentiated organoids for CDX2, an axial progenitor marker (Cambray and Wilson, 2007; van den Akker et al, 2002) and SOX1, a neural tube marker (Pevny et al, 1998). Under identical differentiation conditions, the proportion of SOX1+ versus CDX2+ fates on a coverslip was positively correlated with average organoid density (r = 0.98) (Fig.…”
Section: Resultsmentioning
confidence: 99%